ASEAN+3 Bond Market Guide 2018 Cambodia. (ASEAN+3 Bond Market Guides., 2018)
Among the long-term development objectives of Cambodias Financial Sector Development Strategy 2011 to 2020 were to develop the government securities market and to issue government bonds by the National Treasury. In 2010, the Cambodia Securities Exchange (CSX) was established. The National Bank of Cambodia began issuing negotiable certificates of deposit in 2013, effectively creating an interbank money market.Fundamental legislation and key legislation for the securities market came into effect in 2007 with the adoption of the Law on Government Securities and the Law on the Issuance and Trading of Non-Government Securities. The Securities and Exchange Commission of Cambodia (SECC) was inaugurated in 2008 and it has been gradually establishing the necessary regulatory framework and practices for a corporate bond market. The CSX has been operating since 2010 and features comprehensive listing rules. While the present listings are limited to equities, it is expected that the CSX will allow the listing and trading of debt securities as well.